Edukasi Pencegahan Penyakit Tidak Menular untuk Mewujudkan Sumber Daya Manusia Sehat - Rhoni Ilham Tampubolon; Fitri Aidani Ulfa Hrp (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Non-Communicable Diseases (NCDs) remain a major public health concern due to their increasing prevalence and their impact on quality of life and community productivity. Limited public awareness regarding risk factors and preventive measures contributes to the growing burden of NCDs. This community service program aimed to improve community knowledge and awareness of NCD prevention through health education. The activities consisted of initial interviews to assess participants’ understanding of NCDs, health education sessions focusing on risk factors and preventive strategies, and post-activity interviews to evaluate participants’ responses and understanding. Educational materials emphasized healthy lifestyle practices through the CERDIK approach, which promotes regular health check-ups, physical activity, balanced nutrition, smoking cessation, adequate rest, and stress management. The program increased participants’ awareness of NCD risk factors and encouraged the adoption of healthier behaviors. This initiative is expected to support the development of a healthier and more productive community.